The First Fossil of Nossidiinae From Mid-Cretaceous Amber of Northern Myanmar (Coleoptera: Ptiliidae) - Li, Yan-Da; Newton, Alfred F.; Huang, Di-Ying; Cai, Chen-Yang (Frontiers in Ecology and Evolution, 2022)
Ptiliidae is a group of distinctly miniaturized staphylinoid beetles with scarce fossil record. Here we report a new ptiliid genus and species, Crenossidium slipinskii Li, Newton & Cai gen. et sp. nov., from mid-Cretaceous amber from northern Myanmar. Crenossidium can be attributed to subfamily Nossidiinae based on the hind wing morphology, which has also been confirmed through phylogenetic analyses. Crenossidium differs from other extant nossidiine genera in the combination of the wide apical maxillary palpomeres, posteriorly widest pronotal disc, (almost) contiguous procoxae, fewer setae along wing margin, and multidentate pygidium.